Estimates of tidal mixing in the Indonesian archipelago from multidisciplinary INDOMIX in-situ data. (December 2015) - Koch-Larrouy, Ariane; Atmadipoera, Agus; van Beek, Pieter; Madec, Gurvan; Aucan, Jérôme; Lyard, Florent; Grelet, Jacques; Souhaut, Marc
Abstract: The Indonesian Mixing program (INDOMIX) was designed to quantify the very strong mixing that transforms Pacific waters into isohaline Indonesian Waters in the Indonesian archipelago. The turbulent dissipation rates and associated mixing were estimated and analyzed using a multidisciplinary approach that combines physical and geochemical in-situ observations: (1) direct measurements of the dissipation using a microstructure profiler, (2) use of density-based fine-scale methods applied to CTD and XCTD data, and (3) study of the vertical distribution of natural radionuclides (radium isotopes and actinium-227). Data were collected at five contrasting stations within the Indonesian archipelago, found above energetic straits or in relatively quiescent large basins. Strong instabilities, inversions of the density profiles and a very strong water mass transformation were observed. A wide range of dissipation values were obtained (between [10 −10, 10 −4 ] W kg −1 ) with spots of higher dissipation in the ocean interior correlated with a strong internal tide signal. Both the fine-scale and micro-scale methods allow us to identify very strong energy dissipation levels above the straits, ranging between [10 −7, 10 −4 ] W kg −1, in contrast to lower values at stations further away from the generation sites. The dissipation for the station located in the center of the Halmahera Sea ([10 −9, 10 −8 ] W kg −1 ) is stronger than for the Banda station ([10 −11, 10 −10 ] W kg −1 ), which is even further away from the generation sites. The three approaches agree relatively well and provide vertical eddy diffusivities values ranging between 5×10 −4 and 5×10 −1  m 2  s −1, except in the Banda Sea where values are similar to the ones found in the open ocean (10 −6  m 2  s −1 ). CTD and XCTD profilers (deployed between stations) give estimates of dissipation all along the transit. It is found that enhanced mixing occurs preferentially above rough topography, such as in the Ombai Strait, the Halmahera Sea's northern entrance, the Buru strait and Sumba strait. Finestructure parameters are very sensitive to depth and dissipation, which differs between stations. We recommend more systematic microstructure measurement in order to tune these parameters. Surface mixing, at the base of the mixed layer is found to be very strong with values between [10 −4, 10 −3  m 2  s −1 ]. These results confirm the modeling studies that suggest the occurrence of intensified subsurface mixing which cools the sea surface temperatures and thus strongly affects the mean and variability of the tropical climate. We conclude, therefore, that climate models need to take into account this intensified ocean mixing to properly represent the mean state of the atmosphere and its climate variability. Highlights: The first direct measurements of mixing in region of high energy in the Indonesian seas. Three methods are compared: microstructure, finestructure and from radionuclides. High mixing is found including in the thermocline and in surface layers. Mixing is very heterogeneous. Mixing in the Indonesian seas is critical for tropical climate.